Innovations in phase change materials for diverse industrial applications: A comprehensive review - Reddy, Vennapusa Jagadeeswara; Mohd Fairusham, Ghazali; Sudhakar, K. (Elsevier B.V., 2024)
The need for effective and sustainable thermal management systems is expanding across a variety of industries, and phase change materials (PCMs) have become a flexible alternative to meet this demand. The ability of phase change materials to store significant amounts of heat during their phase transition over a constrained temperature range make them attractive candidates for temperature regulation or energy storage applications in several industrial sectors. This review paper examines recent developments in PCM applications and their significant effects on a range of industries, including building and construction, solar energy storage, electronics, automobiles, pharma and health care, waste heat recovery, electricity generation, water treatment, food and beverages, and textiles. The article starts off by giving a basic overview of PCMs and explaining their distinctive thermal properties, classification, and operating principles. It then delves into the in-depth study, covering the recent advancements of PCM applications. This extensive assessment covers both prospective directions for further study and development as well as the crucial elements influencing the practical application of PCMs. Overall, this article provides a thorough summary of the developments in PCM applications across a range of industries, emphasizing their enormous potential to improve energy efficiency, lower carbon emissions, and promote sustainable development. It is a useful resource for scientists, engineers, and decision-makers working in the domains of thermal engineering, energy management, and materials science. It encourages greater PCM innovation and application for a more sustainable and efficient world.